Nicaragua : Staff Report for the 2005 Article IV Consultation, Seventh, Eighth, and Ninth Reviews Under the Three Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Rephasing and Waiver of Performance Criteria, Financing Assurances Review, and Request for Extension of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses Nicaragua's 2005 Article IV Consultation and Seventh, Eighth, and Ninth Reviews Under the Three Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). The economy continued to perform well, notwithstanding pressure from higher oil prices. Strong performance under the program in 2003-04 allowed Nicaragua to reach the Heavily Indebted Poor Countries completion point in January 2004. Since then, growth has moderated toward 4.1 percent y/y in 2005. Key medium-term challenges include addressing vulnerabilities arising from weak balance sheets, reflected in high levels of debt and dollarization.